ANALYSIS OF PUBLIC MEDIA CONTENT IN COVID-19: A CASE FROM KERALA - Ashok Balasundaram, N. V. Sreedharan, Pratheesh P. Gopinath, S. A. Hafiz, Archana Raghavan Sathyan (Chelonian Research Foundation, 2024)
During the Covid-19 pandemic, governments implemented various communication strategies, some of which were effective in controlling the infection rate and mortality. Kerala, state of India, adopted a unique approach by conducting approximately 200 daily press conferences led by the chief executive, which were broadcasted live across mass and social media. This proactive strategy along with specific nutrition and community support activities contributed to the state's relatively better Covid control.This is credited to have resulted in a repeat mandate in the State Assembly Election of April 2021. This studyanalyses the thematic content of 118 such press conferences (73 hours) and identify the variables controlling the design and content as well as resultant variability. It is seen that the duration and thediverse thematic content of the press conferences were significantly controlled by the rate of spread of the disease. As compared to the first epidemiologically inclined phase, the second electorally proximal phase showed more commitment to themes like covid testing, covid data and an increasing miscellaneous category less related to the pandemic.Miscellaneous content largely addressed reward seeking political economy factors.21% of the thematic variance could be explained by the covid-19 spread and the days remaining to the general elections. It could be seen that the videographic content was largely demand (need for information) and reward/incentive driven, the electoral dividend being the resultant incentive for effective public policy and action for a government during the pandemic phase. Political economy factorsdrove the content design as much as the Covid infection variables as the pandemic phase progressed. Keywords: Social media,Mass media, Content analysis, Effective reproduction number